Community perception on mangrove change issue in Southwest Johor, Malaysia - Noor Shaila Sarmin; Mohd Hasmadi Ismail; Pakhriazad Hassan Zaki; Khairil Wahidin Awang; Monjurur Rahman; Khalid Imran (Science Publishing Corporation Inc., 2018)
Mangroves are important coastal resources that provide both tangible and intangible benefits to the locals as well as others. Rapid coastal development pressures the mangroves to decline continuously. The objective of the study was to comprehend the perception of the locals on mangrove change issue and also to analyze the differences of perceptions among selected socioeconomic factors. Research conducted with a questionnaire survey with 5 point likert type answering options among 196 local respondents from three mukims namely Jelutong, Tanjung Kupang and Serkat. Mean perception score was 3.67 which indicated respondents agreement with the mangrove change issue. The Anova shows the perception score significantly differed among different age groups however there was no difference of perceptions among the rest variables such as race, marital status or education level. The findings of the study concluded that regardless of socioeconomic factors (except age) the respondents were concurred with the situation of mangrove loss in the studied mukims.